THE STRATEGY OF RURAL TOURISM DEVELOPMENT (An Eco-economy and Eco-cultural Approach) - Soeroso, Amiluhur; Susilo, Y. Sri (Journal of Indonesian Economy and Business, 2009)
The research is aimed to analyse the strategy of rural tourism development inÂ Kepuharjo, a village in the foot plain of Merapi Volcano. The data were obtained from 140visitors doing activities surrounding Yogyakarta Special Province with structuredÂ questionnaire; the data was then analysed using conjoint analysis and analyticÂ hierarchical process.The finding shows that the strategy of rural tourism development of Kepuharjo villageÂ is called âsagaâ. Within this strategy, its urgent aspect is keeping an evergreenenvironment, where the object has to be a conservatory value that almost disappears ofÂ environmental change. Besides, it must enrich the attractions, improve quality of amenitiesÂ and get better of accessibilities. The implication of the finding, sustainable development ofÂ rural tourism of Kepuharjo Village, should use both an eco-economy way (designed toÂ mesh with Earths ecosystem instead of disrupting and destroying it) and an eco-cultureÂ work (to respects the traditional knowledge of existence and supports local materials andÂ biodiversity) simultaneously.Keywords: strategy, rural tourism development, eco-economy, eco-culture.